Gene Therapy Rescues Cardiac Dysfunction in Duchenne Muscular Dystrophy Mice by Elevating Cardiomyocyte Deoxy-Adenosine Triphosphate - Kolwicz, Stephen C. (JACC Basic Transl Sci, 2019)
Mutations in the gene encoding for dystrophin leads to structural and functional deterioration of cardiomyocytes and is a hallmark of cardiomyopathy in Duchenne muscular dystrophy (DMD) patients. Administration of recombinant adeno-associated viral vectors delivering microdystrophin or ribonucleotide reductase (RNR), under muscle-specific regulatory control, rescues both baseline and high workload-challenged hearts in an aged, DMD mouse model. However, only RNR treatments improved both systolic and diastolic function under those conditions. Cardiac-specific recombinant adeno-associated viral treatment of RNR holds therapeutic promise for improvement of cardiomyopathy in DMD patients.